Analysis of Person Deixis in Michael Learns to Rock's "Out of the Blue" Song Lyrics - I Made Dwiaji Darmana; I Gusti Ayu Vina Widiadnya Putri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study examines person deixis in Michael Learns to Rock’s 1999 soft rock ballad Out of the Blue. While prior research has explored deixis in speeches, religious discourse, and talk shows, its role in song lyrics particularly emotional ballads remains underexplored. The song’s official lyrics served as the data source. Using Levinson’s (1983) typology for classification and Halliday and Hasan’s (1985) context of situation for interpretation, the research employed a qualitative approach involving careful listening, close reading, and systematic note-taking. The analysis revealed 38 instances of person deixis, primarily singular first- and second-person pronouns, with no plural or third-person forms. This distribution reflects the song’s intimate, direct communication and emphasis on personal emotions. Findings indicate that in lyrical contexts, person deixis enhances emotional closeness, fosters a direct connection between singer and listener, and shapes narrative perspective. The study demonstrates that deixis functions not only grammatically but also artistically, contributing to emotional impact and audience engagement. These insights expand understanding of deixis in non-traditional discourse and suggest its potential value in linguistic, literary, and musicological studies, as well as in language teaching using authentic song materials.